2015
DOI: 10.1590/1516-3180.2014.00241501
|View full text |Cite
|
Sign up to set email alerts
|

The role of diagnostic laparoscopy in gynecology

Abstract: CONTEXT AND OBJECTIVES: Laparoscopy is a diagnostic method that is currently becoming consolidated for therapeutic use. It consists of endoscopically viewing the abdominal cavity. The aim here was to evaluate the indications for diagnostic videolaparoscopy and the intraoperative findings in an endoscopic gynecology clinic at a tertiary-level hospital over the last five years. DESIGN AND SETTING: Retrospective descriptive study on all diagnostic videolaparoscopy procedures of the last five years carried out in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…They found that the agreement between the two modalities was 74% [13]. Agrawal et al [18] and Tognil et al [19] found the probability of tubal occlusion on hysterolaparoscopy to be very low while HSG was normal. Similar results were found in the present study in that no patient showed tubal blockage on chromopertubation when HSG was reported to have tubal spillage of dye.…”
Section: Discussionmentioning
confidence: 98%
“…They found that the agreement between the two modalities was 74% [13]. Agrawal et al [18] and Tognil et al [19] found the probability of tubal occlusion on hysterolaparoscopy to be very low while HSG was normal. Similar results were found in the present study in that no patient showed tubal blockage on chromopertubation when HSG was reported to have tubal spillage of dye.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, laparoscopy has been the gold standard surgical method performed in patients with endometriosis. It allows the definitive diagnosis, through evaluation of the lesions at a macro and microscopic level [40], classifying them according to their severity [41], in addition to being a quick, efficient and minimally invasive procedure, which generally does not involve major complications [40]. Its indication has been reported mainly for women with chronic pelvic pain and infertility, cases in which empirical treatment has not had an effect, cases of drug intolerance and for immediate diagnosis/resolution of the disease [6].…”
Section: Surgical Interventionsmentioning
confidence: 99%
“…There are several surgical procedures. However, it is noteworthy that, although these procedures do not involve major risks, they still exist; with emphasis on infections, hemorrhages and injuries in abdominal pelvic organs (intestine and bladder) [41]. Thus, a thorough clinical analysis is feasible to avoid performing undue procedures, which are relatively invasive and costly.…”
Section: Surgical Interventionsmentioning
confidence: 99%
“…Laparoscopy provided a diagnostic method that is currently becoming consolidated for therapeutic use (7) , and is becoming the gold standard in gynecological surgery (8) . The laparoscopic approach in acute abdomen of gynecologic origin in comparative studies was found to be non-inferior to open surgery (9) .…”
Section: Issn: 2320-5407mentioning
confidence: 99%